The Vulnerability factor analysis of B40 household income group in Southern Region of Kelantan using confirmatory factor analysis / Nor Zuriati Amani Ab Rani...[et.al] - Ab Rani, Nor Zuriati Amani; Ghazali, Rospidah; Siwar, Chamhuri; Isa, Zaidi; Ismail, Mohd Khairi (Division of Research and Industrial Linkages, 2019)
Various factors have contributed to the vulnerability of low-income household groups. Households with the bottom 40 percent income (B40) in the Southern Region of Kelantan are faced with multi-dimensional of vulnerability that cause them to be exposed to uncertain risks and jeopardize their lives. The vulnerability factors of B40 household income group in the Southern Region of Kelantan is determined through three factors, namely economics’ vulnerability, social/physical’s vulnerability, and environment’s vulnerability. The purpose of this study is to determine the vulnerability factors that contribute to the B40 household’s income group in Southern Region of Kelantan. Respondents of this study were 385 people. Survey method using questionnaire instrument was conducted for this study. The data analyzed using IBM-SPSS-AMOS through confirmatory factor analysis (CFA) in combination (pooled). The findings show that all the vulnerability in Southern Region of Kelantan verified through the aspects of vulnerability economic, social/physical and environmental except three items are EK10 (from economic construct), SF1 (from the social/physical construct) and AS1 (from the environmental construct) are eliminated due to lower factor loading values. Main factor vulnerability of economic is loss of main sources of income. Reliance on one source of income makes B40 households vulnerable to shocks and stresses that could potentially affect their lives and difficulties in surviving of life. Natural disaster such as floods also can affect household income and activities especially households are doing agriculture activities as a main job. Vulnerability also linked to poverty. The government's efforts to help lower income households or B40 group before they become poor can reduce the problems of poverty. Government efforts should focused on group either in rural or urban area. In addition, the paradigm shift from understanding poverty after it happens to identify the possibility for the poor should be initiated by the government.